The graded and redefined assessment of strength, sensibility, and prehension version 2 provides interval measure properties - Velstra, Inge-Marie; Fellinghauer, Carolina; Abel, Rainer; Kalsi-Ryan, Sukhvinder; Rupp, Rüdiger; Curt, Armin (Journal of neurotrauma, 2018)
The Graded and Redefined Assessment of Strength, Sensibility and Prehension (GRASSP) is a valid, reliable, and responsive outcome measure to evaluate upper limb function in individuals with tetraplegia. GRASSP generates ordinal total scores; therefore, applicability as an interval level measurement requires testing of its measurement properties. This study examined the metric characteristics with Rasch Analysis to derive interval level scales of the respective GRASSP subtests. The GRASSP was recorded within 10 days, and at 1, 3, 6, and 12 months after cervical spinal cord injury (SCI). Rasch analysis was performed for each GRASSP subscale to assess the following metric assumptions: absence of local item dependency (LID), unidimensionality, monotonicity, item and model fit, reliability, and absence of differential item functioning (DIF) for side (left and right) and examination stage. If these assumptions could not be met, adjustments were undertaken to achieve a good fit to the Rasch model. Seventy-seven individuals with cervical SCI were included (n = 154 arms). Stacking the data for the side (left and right) resulted in a total of 614 observations, which were based on the repeated measurements. With minor adjustments, the GRASSP subscales showed good reliability, item fit, and ordered response options. Local item dependencies were found in the strength and sensibility subscales. Redundancies among some measurement items allowed shortening of the subscales without reasonable loss of reliability. Absence of DIF for the examination stage supported robustness of the subscales over time. The modified GRASSP, now Version 2, subtest scores can be applied as interval level measurements, and the reduction of items within subscales allows for shorter assessment times in clinical studies without degrading metric properties.